Reversible infantile respiratory chain deficiency is a unique, genetically heterogenous mitochondrial disease. Issue 10 (19th September 2011) - Uusimaa, J; Jungbluth, H; Fratter, C; Crisponi, G; Feng, L; Zeviani, M; Hughes, I; Treacy, E P; Birks, J; Brown, G K; Sewry, C A; McDermott, M; et al.
Abstract : Objectives: Homoplasmic maternally inherited, m.14674T>C or m. 14674T>G mt-tRNA Glu mutations have recently been identified in reversible infantile cytochrome c oxidase deficiency (or 'benign COX deficiency'). This study sought other genetic defects that may give rise to similar presentations. Patients: Eight patients from seven families with clinicopathological features of infantile reversible cytochrome c oxidase deficiency were investigated. Methods: The study reviewed the diagnostic features and performed molecular genetic analyses of mitochondrial DNA and nuclear encoded candidate genes. Results: Patients presented with subacute onset of profound hypotonia, feeding difficulties and lactic acidosis within the first months of life. Although recovery was remarkable, a mild myopathy persisted into adulthood. Histopathological findings in muscle included increased lipid and/or glycogen content, ragged-red and COX negative fibres. Biochemical studies suggested more generalised abnormalities than pure COX deficiency. Clinical improvement was reflected by normalisation of lactic acidosis and histopathological abnormalities. The m.14674T>C mt-tRNA Glu mutation was identified in four families, but none had the m. 14674T>G mutation. Furthermore, in two families pathogenic mutations were also found in the nuclear TRMU gene which has not previously been associated with this phenotype. In one family, the genetic aetiology still remains unknown. Conclusions: Benign COX deficiency is better described as 'reversible infantile respiratory chain deficiency'. It is genetically heterogeneous, and patients not carrying the m.14674T>C or T>G mt-tRNA Glu mutations may have mutations in the TRMU gene. Diagnosing this disorder at the molecular level is a significant advance for paediatric neurologists and intensive care paediatricians, enabling them to select children with an excellent prognosis for continuing respiratory support from those with severe mitochondrial presentation in infancy.